Addressing Maqasid-based Waqf for Life on Land (SDG-15): A Delphi Application - Rusydiana, Aam Slamet (Maqasid al-Shariah Review, 2023)
This study aims to determine the opinions and recommendations of experts regarding the waqf model integrated with sustainable development (SDGs) in the 15th goal, namely Life on Land. This research will present the prioritization of waqf models in achieving SDG 15 objectives by considering Maqashid Syariah indicators. Using the Delphi method, the results show that all relative variables have been agreed upon by experts. Furthermore, on the SDGs aspect, the environment element is the top priority with an average score of 8.4. In the aspect of maqash id sharia, the element of preserving bi'ah (environment) is the top priority while in the aspect of waqf model, Waqf & Sukuk model is the top priority for SDG-15 objectives. This research can be utilized as a reference in the implementation of waqf models that can support the realization of SDG-15 objectives by considering Maqashid Sharia with priorities according to the findings. This research is one of the first studies to comprehensively calculate the experts' assessment of waqf models for the achievement of SDG-15 using the Delphi method and its priority recommendations.